IMPLIKASI DIATHESIS PADA STRUKTUR SINTAKSIS BAHASA JEPANG - Yogyanti, Devita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Japanese as a language with quite complex grammatical rules is increasingly visible in terms of its complexity when it comes to the discussion of active, passive, causative, and causative-passive diathesis. This happens because the Japanese language does not use the word to be a sign of the existence of a diathesis, but uses bound morphemes attached to the root of the verb. In connection with this complexity, this paper discussed the complexity of diathesis in Japanese and how the morphemes that make up the diathesis have implications for the structure of Japanese sentences. Data in the form of sentences are analyzed by using agih method and it employs markup reading technique. The results of the sentence analysis are then depicted in a diagram to see the strata level per sentence type, the number of valences, and changes in syntactic functions in each participant in the sentence. From the analysis results, it is known that diathesis in Japanese is formed from the attachment of bound morphemes, which are auxiliary verbs on the root of the word, which is also a bound morpheme. The auxiliary verb passive marker is {-are-} while the causative marker is {-ase-}. Each of these markers has an allomorph according to its class of verbs formed from phonetic adjustments. Furthermore, diathesis in Japanese creates the implications of changing the functions of nouns in sentences and the number of verb valences and core constituents of sentences.Bahasa Jepang sebagai bahasa yang mempunyai aturan gramatikal yang cukup kompleks makin terlihat kompleksitasnya dalam pembahasan mengenai diathesis aktif, pasif, kausatif dan kausatif-pasif. Hal ini terjadi karena bahasa Jepang tidak menggunakan kata untuk sebagai pemarkah adanya diathesis, tetapi menggunakan morfem-morfem terikat yang menempel pada akar verbanya. Sehubungan dengan kompleksitas tersebut dalam tulisan ini dibahas mengenai kompleksitas dhiatesis dalam bahasa Jepang dan bagaimana morfem-morfem pembentuk diathesis tersebut berimplikasi pada struktur kalimat bahasa Jepang. Data berupa kalimat dianalisis dengan metode agih dengan menggunakan teknik baca markah. Hasil dari analisis kalimat kemudian digambarkan dalam suatu diagram untuk melihat tingkatan strata per jenis kalimat, jumlah valensi, dan perubahan fungsi sintaksis pada setiap peserta yang ada dalam kalimat. Dari hasil analisis diketahui bahwa diatesis dalam bahasa Jepang dibentuk dari pelekatan morfem-morfem terikat yang merupakan kata kerja bantu pada akar kata yang juga merupakan morfem terikat. Kata kerja bantu penanda pasif adalah {-are-} sedangkan penanda kausatif adalah {-ase-}. Masing-masing penanda tersebut mempunyai alomorf  menurut golongan verbanya yang dibentuk dari penyesuaian fonetis. Selanjutnya, diathesis dalam bahasa Jepang menimbulkan implikasi berubahnya fungsi-fungsi nomina di dalam kalimat dan jumlah valensi verba serta konstituen inti kalimat.